2018
DOI: 10.1155/2018/3942301
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Factors Associated with Anemia among Pregnant Women Attending Antenatal Clinic at St. Paul’s Hospital Millennium Medical College, Addis Ababa, Ethiopia

Abstract: Background In pregnancy, anemia is an important factor associated with an increased risk of maternal, fetal, and neonatal mortality, poor pregnancy outcomes, and impaired cognitive development, particularly in developing countries like Ethiopia. This study aimed to assess prevalence and factors associated with anemia among pregnant women attending antenatal clinic at St. Paul's Hospital Millennium Medical College, Addis Ababa, Ethiopia. Method A cross-sectional health facility based study was conducted on 284 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
39
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(63 citation statements)
references
References 24 publications
16
39
8
Order By: Relevance
“…The current study showed that, the prevalence of anemia was 2.18 times higher at third trimester [AOR (95% CI) = 2.18 (1.40 -3.40), P = 0.001] than first trimester. The study finding was well-matched with other studies conducted at Adigrat General Hospital, Northern Ethiopia [5], Southern Ethiopia [6], JigJiga, Eastern Ethiopia [13], Addis Ababa, Ethiopia [27], Southern Ethiopia [31], and Tikur Anbessa Specialized Hospital, Addis Ababa Ethiopia [32]. Pregnant women's birth interval having less than two years [AOR (95% CI) = 2.87 (1.51 -5.44), P = 0.001] were 2.87 times more likely to be anemic compared to those with birth interval more than two years.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The current study showed that, the prevalence of anemia was 2.18 times higher at third trimester [AOR (95% CI) = 2.18 (1.40 -3.40), P = 0.001] than first trimester. The study finding was well-matched with other studies conducted at Adigrat General Hospital, Northern Ethiopia [5], Southern Ethiopia [6], JigJiga, Eastern Ethiopia [13], Addis Ababa, Ethiopia [27], Southern Ethiopia [31], and Tikur Anbessa Specialized Hospital, Addis Ababa Ethiopia [32]. Pregnant women's birth interval having less than two years [AOR (95% CI) = 2.87 (1.51 -5.44), P = 0.001] were 2.87 times more likely to be anemic compared to those with birth interval more than two years.…”
Section: Discussionsupporting
confidence: 88%
“…According to the World Health Organization classification, the prevalence of anemia among pregnant women in this study was a severe public health problem [17] [28] [29]. The prevalence determined in this study area was comparable with other studies reported in different countries: Bangladesh (59%), Bhutan (59%), and Sri Lanka (60%) [25], China (58.6%) [18], Malaysia (57.4%) [27]; higher than Republic in Korea (30.2%), South Africa (19.7%) [15], in rural area of Southern Ethiopia (29%); and lower than India (87.2%), Pakistan (90.5%) [27] and Nepal (73%) [9]. Socio-demographic factors are associated with anemia among pregnant women [22].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The magnitudes of association for pertinent factors such as advanced trimesters, multiple gestations, IDA prior to pregnancy, and hematological diseases other than IDA, were relatively strong (adjusted odds ratio over 2). The results were consistent with studies on non-Chinese populations [28][29][30][31], and have important implications for managing pregnant women with these characteristics who may be at elevated risk. The sensitivity analysis by excluding those with previously diagnosed IDA or anemia have further confirmed the apparent adverse effect of these factors on the development of anemia or IDA.…”
Section: Risk Factors For Anemia and Idasupporting
confidence: 88%
“…14,15 In this study, there were 7.4% cases of anaemia which is closely comparable with studies in Ethiopia 9.7%, 16 Sudan 10%, 17 and Ethiopia 11.6%. 18 The prevalence is lower than the worldwide prevalence of anemia in pregnancy that has been estimated at 40.1%. 1 Our prevalence, however, is lower than the national prevalence of Uganda (30.4%) 19 showing spatial distribution of anaemia from region to region and relying on the study methods employed.…”
Section: Prevalence Of Anemiamentioning
confidence: 92%